Relationship Between Trunk Control Ability and Respiratory Function in Stroke Patients: A Scoping Review and Meta-Analysis - Hsiang-Chu Pai; Chia-Chi Li (Elsevier, 2023)
summary: Purpose: Hemiparesis in stroke survivors has been reported to affect respiratory function. The relationship between trunk control and respiratory function, however, is not well understood. We aimed to map the state of the association between the trunk and respiratory function as well as evaluate the effect of a respiratory function training intervention on trunk control for stroke survivors. Methods: A scoping review and meta-analysis of observational and interventional studies were performed. Cochrane Library, CINAHL with Full Text (EBSCO), Medline (Ovid), and PubMed were searched using the terms stroke, respiratory, and trunk control. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist was used to examine the sections of each report. Results: A total of 102 studies were identified, of which 12, published between 2011 and 2022, were included in the meta-analysis or narrative synthesis. Three studies were included in the meta-analysis of the correlation between trunk control and respiratory function parameters (forced vital capacity [FVC], forced expiratory volume during the first breath [FEV1], maximal inspiratory pressure [MIP], and maximal expiratory pressure [MEP]) with effect sizes (Fisher's z) for all outcomes, which ranged from small to intermediate (between 0.21 and 0.39). Furthermore, five studies were included in the meta-analysis of the effect of respiratory function training intervention on trunk control. An overall effect size (Cohen's d) of 1.47 corresponds to a large effect. We also found significant improvements in MIP and MEP but not in FVC and FEV1 for stroke survivors with the interventions. Conclusions: Respiratory training, use of diaphragmatic resistance exercise or abdominal breathing, use of a pressure threshold-loading device, and the performance of functional strengthening exercises for the trunk muscles were found to increase patients' trunk control and improve their respiratory muscle strength.